Induction of immunological tolerance as a therapeutic procedure - Waldmann, H; Howie, D; Cobbold, S (American Society for Microbiology, 2016)
A major goal of immunosuppressive therapies is to harness immune tolerance mechanisms so as to minimize unwanted side effects associated with protracted immunosuppressive therapy. Antibody blockade of lymphocyte coreceptor and costimulatory pathways in mice has demonstrated the principle that both naive and primed immune systems can be reprogrammed toward immunological tolerance. Such tolerance can involve the amplification of activity of regulatory T cells, and is maintained through continuous recruitment of such cells through processes of infectious tolerance. We propose that regulatory T cells create around them microenvironments that are anti-inflammatory and endowed with enhanced protection against destructive damage. This acquired immune privilege involves the decommissioning of cells of the innate as well as adaptive immune systems. Evidence is presented that nutrient sensing by immune cells acting through the mammalian target of rapamycin (mTOR) pathway provides one route by which the immune system can be directed toward noninflammatory and regulatory behavior at the expense of destructive functions. Therapeutic control of immune cells so as to harness metabolic routes favoring dominant regulatory mechanisms has offered a new direction for immunosuppressive therapy, whereby short-term treatment may be sufficient for long-term benefit or even cure.